STRATEGI BAURAN PRODUK IKONIK UMKM ALOEVERA DI KOTA PONTIANAK - Nurcholifah, Ita (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2020)
One of the areas and cities that have natural resources is the city of Pontianak. These natural resources are in the form of aloe vera (Aloe vera). Aloe vera is a plant that is easy to grow on peatlands in the city of Pontianak and has high benefits and economic value. So that this plant can be used as various types of food and beverage processing. The development of MSMEs in Pontianak City, of course, must be supported by an effort to keep the business running and progress in business, especially in terms of income, so that gradually the UMKM can